Determinantes e preditores de óbitos infantis, no estado de Goiás, 2012.Uso de linkage de bases de dados dos sistemas de informações em saúde do SUS - Carvalho, Simone Resende de (2017)
Introduction: Reducing infant mortality is a challenge for health services and society as a whole. They demand changes in the socioeconomic conditions of the population, reduction of inequalities, and also access and quality of health services, both primary care and specialized outpatient and hospital services. In the evaluation of the studies on infant mortality in the state of Goiás, little research was done with data linkage. Objective: To estimate the magnitude and to evaluate the factors associated with infant mortality, and their respective components, in the live birth cohort of mothers residing in Goiás in 2012. Methodology: Longitudinal analytical study of a retrospective cohort based on secondary data. The three databases were identified for the identification of infant deaths and hospitalizations of mothers and children. A descriptive analysis was performed with estimates of infant death probabilities and their components, as well as an analytical approach using bivariate and multivariable logistic regression using hierarchical models to identify the associated factors. Odds Ratios and respective 95% confidence intervals were estimated. Results: The probability of MI was 12, 9 deaths in children under one year per thousand live births in Goiás, this result represents the best estimate of infant mortality for Goiás in 2012. The study identified association as a risk factor in MI In the categories of gestational age, birth with anomalies, unsatisfactory apgar index in the fifth minute and weight less than 1,500 grams, which may be associated to insufficient quality of health care in prenatal, childbirth and puerperium. Conclusions: From the results of this study, the identification of the pregnant women who present these factors can be incorporated in the routine of the health services and basic and hospital care, allowing a differentiated attention to the groups of pregnant women exposed to these risk factors and predictors, Prevent child deaths.